2010
DOI: 10.1063/1.3517255
|View full text |Cite
|
Sign up to set email alerts
|

Photoreflectance analysis of a GaInP/GaInAs/Ge multijunction solar cell

Abstract: We have analyzed the photoreflectance spectra of a GalnP/GalnAs/Ge triple junction solar cell. The spectra reveal signatures from the window layer and middle and top subcells included in the stack. Additional contributions from the multilayer buffer introduced between the mismatched bottom and middle cells have been detected. Franz-Keldysh oscillations (FKOs) dominate the spectra above the fundamental bandgaps of the GalnP and GalnAs absorbers. From the FKO analysis, we have estimated the dominant electric fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Additionally, also photoreflectance (PR) measurements were performed 17. A light beam from a tungsten lamp (up to 250 W) is passed through a monochromator (1/8 m Cornerstone‐Newport) and focused by optical lenses on the sample surface.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, also photoreflectance (PR) measurements were performed 17. A light beam from a tungsten lamp (up to 250 W) is passed through a monochromator (1/8 m Cornerstone‐Newport) and focused by optical lenses on the sample surface.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis, properties and applications of group IV nanoparticles have attracted great interest over the past several years (Fan & Chu, 2010). The size tunable optical and electric properties make Ge and other group IV elements including Si and C attractive for multi-junction solar cells (Cá novas et al, 2010;Guter et al, 2009), photodectors (Assefa et al, 2010) and field-effect transistors (Pillarisetty, 2011;Kamata, 2008). Moreover, potential applications of Ge nanocrystals (NCs) on printing electronics (Kim et al, 2010) and organic-inorganic hybrid photoelectric devices (Xue et al, 2011) as well as in biological imaging (Lambert et al, 2006(Lambert et al, , 2007 have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Group IV semiconductor nanocrystals (NCs) have attracted much attention in recent years for applications in different areas, including photodetectors,1–3 field‐effect transistors,4, 5 lithium‐ion batteries,6, 7 and solar cells 8, 9. In particular, germanium NCs have drawn special attention because of its inherent properties: Firstly, Ge is a narrow bandgap semiconductor with a bulk bandgap of 0.67 eV at 300 K, which can be easily tuned by quantization to technologically important wavelengths.…”
mentioning
confidence: 99%